Stimulating Children in Enhancing Spirituality through the Exemplary Story of Ants - Erna Budiarti (Perhimpunan Intelektual Muslim Indonesia, 2023)
It is important for Early Childhood to be stimulated by providing support in practising activities directly carried out by children in order to make it a religious experience. The purpose of stimulating Early Childhood is to increase Spirituality through the example of teachers and meaningful interactions about the beauty of diversity through exemplary stories. This research was conducted at Nurul Aulia Kindergarten Depok with a qualitative descriptive research method with a case study approach. The results of the study show that through the story of the example of ants and interactive dialogue, it is known that the implications of stories about theexample of ants in Early Childhood are very effective in building spiritual character and have an impact on the attitudes and behavior of children who have love for their religion, are able to identify problems and find solutions.